Improving Economic Learning Outcomes Through Problem-Based Learning Using Augmented Reality Media - Rahman, Dhea Aulia; Prasetyo, Prakoso Dwi; Herawan, Endang; Putri, Dian Permana (LPPPIPublishing, 2024)
This study discusses the improvement of economic learning outcomes through a problem-based learning approach using Augmented Reality (AR) media. With a focus on the application of innovative concepts in education, this study explores how the combination of an effective problem-based learning approach and engaging AR technology can improve students' understanding of economic concepts. The results show that the use of AR in economics learning can significantly improve student engagement, concept understanding, and learning outcomes. In addition, the problem-based learning approach also proved effective in improving students' critical thinking and problem-solving skills. Despite challenges related to technology availability and teacher training, the conclusions of this study emphasize the importance of integrating AR technology and innovative learning approaches in creating a more engaging and effective learning environment in the context of economics education. Further research is needed to optimize the use of this technology and evaluate its effectiveness in various educational contexts.